Effects of exogenous application of salicylic acid on drought performance of medicinal plant, Fritillaria przewalskii Maxim - Ma, Ruili; Xu, Shengrong; Chen, Yuan; Guo, Fengxia; Wu, Rui; Okyere, Samuel; Wang, Fusheng; Jing, Yanming; Wang, Xingzheng (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2019)
This study investigated the effects of salicylic acid (SA) foliar application on Fritillariaprzewalskii under drought stress condition. Plants were subjected to three irrigation regimes, 75-80% control (CK), 60-65% medium stress (M) and 40-45% severe stress (S) of the field capacity and three levels of SA, 0.0, 0.5 and 1.0 mM. Relative water content (RWC), proline content, total soluble carbohydrates, chlorophyll “a” (Chl a), chlorophyll “b” (Chl b), chlorophyll “a + b” (Chl a + b), carotenoids contents, malondialdehyde (MDA) contents and activities of several antioxidant enzymes such as superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), glutathione reductase (GR) and ascorbate peroxidase (APX) activity were measured. RWC, soluble carbohydrates, Chl b, Chl a + b, MDA content and activities of antioxidant enzymes (SOD, POD, CAT, GR and APX) were significantly affected by water deprivation without SA. Exogenous SA significantly increased the content of RWC, total leaf soluble carbohydrates, leaf proline and Chl b at moderate water deficit and severe water deficit. MDA content was decreased significantly by exogenous SA. The activities of antioxidant enzymes (SOD, POD, CAT, GR and APX) were also significantly affected by exogenous SA. However, the content of Chl a, Chl a + b, and carotenoids were not significantly affected by exogenous SA.